The locus for resistance to Asian soybean rust in PI 587855. (11th July 2016) - Yamanaka, Naoki; Morishita, Mio; Mori, Tomomi; Muraki, Yukie; Hasegawa, Midori; Hossain, Md. Motaher; Yamaoka, Yuichi; Kato, Masayasu
Abstract: Asian soybean rust (ASR) caused by Phakopsora pachyrhizi is one of the most serious soybean ( Glycine max ) diseases in tropical and subtropical areas. A soybean line, PI 587855, showed a resistance phenotype against ASR pathogens in Japan and South America at high frequency; however, little is known of the genetic control of this resistance and chromosomal location of the corresponding locus. Therefore, the aim of this study was to study the inheritance of PI 587855 resistance and map the corresponding locus with SSR markers aiming to use the linked markers in marker‐assisted selection. In the segregating population, resistance to ASR appeared to be controlled by a single dominant gene. The ASR resistance locus was mapped near to the chromosomal region where the resistant loci, Rpp1 and Rpp1‐b, were previously mapped. Comparative genetic mapping and disease reaction profiles of other seven lines carrying Rpp1 or Rpp1‐b to four Brazilian ASR isolates revealed that the resistance reaction exhibited by PI 587855 was similar to that of Rpp1‐b ‐carrying varieties which have useful resistance to South American ASR strains.